Nanostructure‐Mediated Photothermal Effect for Reinforcing Physical Killing Activity of Nanorod Arrays - Guannan Zhang; Zehao Li; Menlin Sun; Ying Lu; Jianbo Song; Wangping Duan; Xiaobo Huang; Ruiqiang Hang; Xiaohong Yao; Paul K Chu; Xiangyu Zhang (Advanced Science)
Abstract The physical killing of bacteria based on surface topography has attracted much attention due to the sustainable and safe prevention of biofilm formation. However, the antibacterial efficiency of biomedical implants derived solely from nanostructures or microstructures is insufficient to combat bacteria against common infections, such as methicillin‐resistant Staphylococcus aureus with thick cell walls. Herein, photothermal therapy is carried out in the presence of nanorod arrays to mitigate infection of biomedical implants. Different from traditional photothermal therapy relying on a photosensitizer, the photothermal effect is mediated by light traps rendered by the nanorod arrays, and consequently, the photosensitizer is not needed. Finite element simulations and experiments are performed to elucidate the light‐to‐thermal conversion mechanism. This photothermal platform, in conjunction with thermosensitive nitric oxide therapy, is applied to treat titanium implant infection. The nanostructure‐mediated photothermal effect destroys bacterial cell walls by inhibiting peptidoglycan synthesis and increasing the membrane permeability by affecting fatty acid synthesis. Furthermore, the nanorods synergistically puncture the bacterial membrane easily as demonstrated by experiments and transcriptome analysis. The results provide insights into the development of efficient antibacterial treatment of implants by combining nanostructures and photothermal therapy.